Local Diversity and Biting Pattern of Anopheles Species in Southern Minahasa - Pinontoan, O. R.; Supadmanaba, I. G. P.; Manuaba, I. B. A.; Sukrama, I. D. M.; Manuaba, I. B. P. (Interdisciplinary Perspectives on Infectious Diseases, 2017)
Background. To optimize the preventive measures of malaria, it is important to synchronize the efforts with the behavior of local Anopheles species. However, the data of Anopheles species and their behavior in Indonesia is still lacking. Method. Explorative research was conducted from April to September 2016 in Southern Minahasa district. The Anopheles mosquito was baited by using animal and human (indoor or outdoor) from 18.00 to 06.00 hours. Then, the species were identified and Man Biting Rate (MBR) and Man/Animal Biting per Hour (MBPH) were calculated followed by statistical analysis by using SPSS 17. Result. The data showed that the dominant species in Southern Minahasa were An. barbirostris, An. kochi, and An. vagus. An. vagus was found to be zoophilic and An. barbirostris was showing strict anthropophilic characteristics. Meanwhile, An. kochi feeds on both human and animal. The MBR of An. kochi was found to be the highest (P<0.005), but its MBPH only significantly exceeded that of An. vagus. All species tend to be more active during the early evening. Conclusion. An. barbirostris, An. kochi, and An. vagus were the dominant Anopheles species in Southern Minahasa. Further research is needed to determine the Plasmodium infestation rate of these species.